Root exudates and microbial community structure characteristics of mango under soil borne diseases - Xie, Yongjun; Qin, Wenlian; Wang, Mengjia; Pan, Xiaozhuo; Qin, Xiaojie; Wang, Yibing (Frontiers in Microbiology, 2025)
IntroductionAs the years of mango cultivation progress, pathogens invade the soil, leading to the development of soil borne diseases. These diseases not only change the physical and chemical properties of the soil but also influence the diversity and composition of soil microbes, ultimately impeding the development of the mango industry. In view of this, this study aimed to explore the correlations among the physical and chemical properties of mango root soil, root exudates, soil microbial community and soil borne diseases.MethodsHealthy, diseased and severely diseased mango root soil samples were taken as the investigation objects. The main research methods were: (1)Testing seven soil physicochemical properties, such as total phosphorus and total potassium, in rhizosphere soil. (2) We determined the phenolic acid content in mango rhizosphere soil using high-performance liquid chromatography (HPLC). (3) Soil microbial communities were analyzed using second-generation high-throughput sequencing technology. (4) The characteristics and response mechanisms of changes in soil microbial community structure were analyzed using multivariate statistical methods, such as redundancy analysis (RDA) and correlation analysis, in combination with physical and chemical environmental factors. (5) PICRUSt2 analysis of microbial community function under soil borne diseases.ResultsSoil borne disease had profound impacts on soil physicochemical properties, root exudates (phenolic acid) and microbial community structure. On one hand, with the development of soil—borne disease, the mango’s ability to absorb foreign nutrients is weakened, leading to the accumulation of nutrients in the root soil, which significantly increases total phosphorus, total potassium, alkaline hydrolysis nitrogen, acid—soluble phosphorus, available potassium, organic matter and pH value. On the other hand, soil borne disease also increased the secretion of phenolic acid in mango root, with significantly increased concentrations of vanillic acid, ferulic acid, salicylic acid and coumaric acid. High-throughput sequencing results showed that soil-borne diseases were followed by a decrease in bacterial diversity, an increase in fungal diversity, and the accumulation of pathogenic microorganisms such as Fusarium in the soil. In addition, the physical and chemical properties of the soil as well as phenolic acid exudates also influenced microbial community functioning, particularly with respect to genetic information processing, metabolism and biological systems.DiscussionIn this study, we investigated the mechanism of soil-borne diseases in mango by studying the response mechanism of soil-borne diseases with root secretion and microbial community. It provides theoretical support for the sustainable development of mango industry.